Information of the Seventh Republican Conference of the Mathematicians of Lithuanian SSR - Journal , Lithuanian Mathematical (Lithuanian Mathematical Journal, 1966)
Информация о Седьмом республиканском совещании математиков Литовской ССР Informacija apie Septintąjį respublikinį Lietuvos TSR matematikų pasitarimą